Performance Determinants Of Sandwich Generation Employees At Work - Ni Made Tia Wulandari; A.A.N. Oka Suryadinatha Gorda (Eduvest - Journal of Universal Studies, 2024)
This study investigates the performance determinants of sandwich generation employees, who face the dual responsibilities of caring for children and elderly parents while working. Role conflict, workload, and toxic productivity are explored as factors influencing performance. The research utilizes quantitative methods, employing regression analysis to examine the relationships between these variables and employee performance. Data collection is conducted through questionnaires distributed via Google Forms. The study focuses on the Badung Regency in Bali, a region with a significant economic presence. The population consists of sandwich generation individuals aged 30-60, residing and working in Badung Regency. The results indicate that role conflict, workload, and toxic productivity negatively impact employee performance. Additionally, job satisfaction is found to moderate the effects of role conflict, workload, and toxic productivity on performance, suggesting that higher job satisfaction can mitigate these negative influences. The findings provide insights into the challenges faced by sandwich generation employees and highlight the importance of addressing these factors to enhance performance in the workplace.